Transition to practice: creation of a transitional rotation for radiation oncology - Dahn, Hannah; Watts, Karen; Best, Lara; Bowes, David (Canadian Medical Education Journal, 2018)
Background: Implementation of Competence by Design (CBD) will require residency training programs to develop formalized “Transition to Practice” (TTP) experiences. A multidisciplinary group of Radiation Oncology stakeholders from tertiary care centres in Atlantic Canada were surveyed regarding a proposed TTP rotation. Methods: The survey asked participants to quantitatively rank various learning objectives based on defined CanMEDS skills that are expected to be mastered by a graduating resident. Mean perceived importance scores were calculated for each objective as well as for their CanMEDS category. Specific written qualitative feedback was also collected. Results: The survey was circulated to 59 participants with a response rate of 73%. The three objectives with the highest mean importance score were “Independently assessing and managing patients seen in consultation,” “Developing and demonstrating communication skills with patients at an advanced level,” and “Independently assessing and managing follow up patients,” respectively from highest to lowest. The CanMEDS roles with the highest importance score was “Communicator.” Conclusion: Quantitative and qualitative data from a multidisciplinary survey based on CanMEDS roles guided the implementation of a TTP rotation for PGY-5 residents at a tertiary care centre in Atlantic Canada. These results may be relevant to other training programs developing TTP experiences.